Tuning Adsorption-Induced Responsiveness of a Flexible Metal-Organic Framework JUK-8 by Linker Halogenation - Rortocki, Kornel; Formalik, Filip; Bon, Volodymyr; Krawczuk, Anna; Goszczycki, Piotr; Kuchta, Bogdan; Kaskel, Stefan; Matoga, Dariusz (Chemistry of Materials, 2022)
Flexible stimuli-responsive metal-organic frameworks have become promising candidates for numerous applications in gas-related technologies; however, the methods of fine tuning their responses are still limited and sought after. In this work, we demonstrate control over the adsorption properties of a flexible platform by incorporating halogen substituents (X = F, Cl, Br, I) into an eightfold interpenetrated isoreticular series [Zn(oba)(X-pip)]n (JUK-8X; X-pip = 4-pyridyl-functionalized benzene-1,3-dicarbo-5-halogenohydrazide; oba2- = 4,4′-oxydibenzoic carboxylate). The introduced halogen atoms allow for precise tuning of CO2 gate-opening pressures from p/p0 = 0.08 for the parental JUK-8 to 0.78 for the chlorine-functionalized JUK-8Cl. The presence of fluorine or chlorine substituent in the X-pip linker practically does not influence the maximum molar CO2 uptake as compared to JUK-8, whereas larger bromine or iodine atoms increase this uptake by 59 and 48%, respectively. Utilizing in situ powder X-ray diffraction (PXRD) during CO2 adsorption for a model JUK-8F, we propose a detailed mechanism of phase transitions including positions of the adsorbed gas molecules for the two loaded phases. Density functional theory calculations supported by in situ PXRD measurements at a saturation pressure shed light on the unusual CO2 adsorption properties of JUK-8Br and JUK-8I. Overall, our report demonstrates the use of halogen interactions for the control of a gas-responsive system and provides insightful guidance for the further development of flexible, adaptable materials.
CRIS-Team Scopus Importer:2023-03-20